Negotiations and bargaining: introduction - Craver, Charles B. (Henry Stewart Talks, 2011)
Business persons & lawyers negotiate constantly, Negotiations are quite structured, Factors possessed by skilled negotiators, Negotiation myths, Why many persons dislike negotiating, Must learn from past interactions, Need to develop proficient negotiation skills
Reviewed at 2020/03/30